Meat quality and color of abdominal fat of broilers fed diets containing cashew nut meal treated with antioxidant - doi: 10.4025/actascitechnol.v35i1.9564 - Lopes, Irani Ribeiro Vieira; Zapata, Jorge Fernando Fuentes; Freitas, Ednardo Rodrigues; Souza, Daniela Vieira de; Viana Neto, José Lopes; Lima, Janice Ribeiro (Acta Scientiarum. Technology, 2012)
This experiment aimed to assess the influence of diets containing cashew nut meal stored for 35 days and treated at different storage times with 500 ppm butylated hydroxytoluene on the characteristics of breast meat and abdominal fat. The experiment followed a completely randomized design. Treatments consisted of diets containing: untreated cashew nut meal; cashew nut meal treated with antioxidant on zero day of storage, and cashew nut meal treated with antioxidant on 21st day of storage. At 42 days old, broilers were slaughtered. Breast and abdominal fat of each bird were identified, weighed, frozen stored for subsequent analysis. The variables studied were: pH, water holding capacity, cooking losses and shear force, in the meat and color of the meat and of the abdominal fat. Treatments did not affect (p > 0.05) the evaluated parameters. However, the yellowness (component b*) of the abdominal fat was higher in birds fed the diet containing meal treated with antioxidant at storage day zero. In conclusion, the cashew nut meal can be stored for 35 days without antioxidant, but in order to achieve intense yellowness in abdominal fat of broilers 500 ppm antioxidant addition is required, at the beginning of storage. Â 